Population travel increases the risk of Plasmodium falciparum infection in the highland population of Gardula Zone, South Ethiopia: A longitudinal study. - Muluken Assefa; Fekadu Massebo; Temesgen Ashine; Teklu Wegayehu (PLoS ONE)
Population movement influences malaria epidemiology and can be a threat to malaria control and elimination. In Ethiopia, highland dwellers often travel to lowland areas where malaria is endemic. The current study aimed to assess the incidence of malaria and risk factors among dwellers in two highland villages of the former Dirashe District (now Gardula Zone), South Ethiopia. A longitudinal study was conducted from 10/05/2018 to 30/11/2018. A total of 1672 individuals from 329 households were recruited via a systematic random sampling technique. Blood samples were collected from all consented family members. The study participants were interviewed via a pretested questionnaire. Bivariate and multivariate analyses were conducted to determine risk factors associated with malaria infection. A total of 4,884 blood samples were screened for malaria parasites in three rounds of surveys. Among those, 82 slides were positive for malaria parasites, 70 (85%) of which were collected during active case detection, and the remaining 12 (15%) were captured by passive case detection. Plasmodium falciparum accounted for 69.5% (57), and the remaining 30.5% (25) were Plasmodium vivax. The incidence of malaria in the highlands of Dirashe District was 0.2 infections per person-year at risk. Inhabitants who traveled to lowlands in the past 30 days (AOR = 2.60, 95% CI: 1.27-5.33) had a significantly greater risk of contracting Plasmodium falciparum infection. Those people traveling in May and November, those participants who had no formal education and agricultural workers, had a greater risk of developing malaria infection. Low bed net ownership (63.2%) and use (52.9%) have been documented among highland populations. This study revealed that people who travel from highlands to malaria-endemic lowland areas for agriculture are at increased risk of developing malaria. Hence, malaria interventions targeting travelers should be implemented to reduce the imported malaria burden in highlands.